Link Length Optimization of A Biomimetic Robotic Fish Based on Big Bang - Big Crunch Algorithm - Bal, Cafer; Korkmaz, Deniz; Koca, Gonca Ozmen; Ay, Mustafa; Akpolat, Zuhtu Hakan (Ieee, 2016)
This paper is concerned with the link length optimization method of a biomimetic Carangiform robotic fish with multi-link propulsion mechanism. Motion characteristic of a real fish depends on the body traveling wave and propulsion mechanism of the robotic fish should imitates the traveling wave function. In order to imitate the body traveling wave with minimum error, intersection method is used and Big Bang - Big Crunch (BB-BC) optimization algorithm is adapted to this method. BB-BC algorithm is a heuristic and evolutionary optimization method. BB-BC is preferred in many nonlinear engineering problems because of the low computation time and very fast convergence speed. As a results, optimum link lengths and endpoints of the each joint are determined by using this combined method. Numerical results show that precise fitting effects and link length optimization can improve the propulsion efficiency of the robotic fish. Also, optimum links are proportioned according to actual size of a real Carangiform carp fish in the main axis and free swimming gaits of the real carp are proved.
21st International Conference on Methods and Models in Automation and Robotics (MMAR) -- AUG 29-SEP 01, 2016 -- Miedzyzdroje, POLAND
Keywords: robotic fish; Big Bang - Big Crunch; optimization; biomimetic; link length optimization